The Expression Profile, Clinical Application and Potential Tumor Suppressing Mechanism of hsa_circ_0001675 in Head and Neck Carcinoma - Cao, Yujie; Ye, Dong; Shen, Zhisen; Li, Zan; Li, Qun; Rong, Hao (Frontiers in Oncology, 2022)
Purpose This study sought to identify circular RNAs (circRNA) that participate in the regulation of head and neck cancer (HNC), analyze their clinical application, and predict their molecular mechanism during HNC. Materials and Methods High-throughput sequencing was used to analyze circRNA expression in 18 matched HNC and adjacent normal tissues. Target circRNAs with significantly differential expression were obtained. In 103 HNC and adjacent normal tissues, real-time fluorescent quantitative PCR (qRT-PCR) was used to verify the differential expression of target circRNAs. This data was combined with clinicopathological information to analyze the diagnostic value of target circRNA. Bioinformatics was used to find target circRNAs that acted as competitive endogenous RNA (ceRNA) and construct a circRNA-miRNA-mRNA regulatory network. mRNA expression was verified by immunohistochemistry (IHC). Results A total of 714 differentially expressed circRNAs were detected in HNC, and the low expression of hsa_circ_0001675 was particularly significant (fold change [FC] = -4.85, P = 6.305E-05). hsa_circ_0001675 had significantly lower expression in HNC than in normal tissue (P < 0.01). Low hsa_circ_0001675 expression was positively associated with tumor invasion and clinical staging (P < 0.05), and its area under the ROC curve (AUC) was 0.7776. Low hsa_circ_0001675 expression also correlated with the overall survival (OS) rate and the progression-free survival (PFS) rate of HNC patients (P < 0.001). Bioinformatics was used to construct a ceRNA network of hsa_circ_0001675 with six differentially expressed miRNAs (hsa-miR-330-5p, hsa-miR-498, hsa-miR-532-3p, hsa-miR-577, hsa-miR-1248, and hsa-miR-1305) and 411 differentially expressed mRNAs and found that the neuroactive ligand-receptor interaction, and the cAMP and calcium signaling pathways were particularly enriched. Further bioinformatics and IHC analysis showed that miR577/TESC is the likely downstream signaling pathway for hsa_circ_0001675. Conclusion This study showed that hsa_circ_0001675 is downregulated in HNC and could be an effective biomarker for HNC diagnosis. In addition, hsa_circ_0001675 may have a potential ceRNA mechanism and suppress HNC disease progression through the hsa_circ_0001675-miRNA-mRNA axis.